Orkestra Tong Sampah Pembelajaran: Hubungan Simbiotik Fungsional antara Ajaran Islam dengan Kegiatan Pembelajaran - Anwar Sholihin (PROGRESSA: Journal of Islamic Religious Instruction, 2017)
To be "educated" today requires mastery of core subjects, 21st century themes, and 21st century skills. To help students achieve skills in 21st century skills, teachers and administrators need an educational support system that strengthens their teaching capacity, leadership and management and both students and educators need a conducive learning environment for satisfying results. In implementing the teaching and learning of Islamic education, Islamic education teachers are seen in the community as the best example or role model that forms people who are moral and pious. This study aims to identify and explain the functional symbiotic relationship between Islamic teachings and learning activities. The conclusions of this paper are the elements described in this section as "21st century student results" (represented by pelangi) are the skills, knowledge, and skills students must master to succeed in work and life in the 21st century. While in Islam the Prophet Muhammad is a person who teaches: 1) by example and example with the principle of "Talkless, Do More", 2) a person who constantly learns. 3) teaching with stories to learn from, 4) teaching with dialogue, practicing thinking and analyzing, 5) teaching with portrayals. If one does not run, the orchestra of the learning trash can is running